(untitled) (Medico Legal Update, 2020)
Objectives: To identify the effect of hearing impairment on children behavior in daily activities and communication with peers and problems facing teachers of HI children in Iraqi environment. Methods : the strength and difficult questionnaire (SDQ) was used to measure the behavioral, and peer problems questionnaire to measure communication disorders of children with HI based on parents and teachers in (209) children (123) HI and (86) normal hearing control group. Results: on parent teacher questionnaire significantly higher behavioral problems for HI children compared with control group (p-value 0.043< alpha value 0.05) and (chi-square 7.321) so increase the emotional problems (p-value 0.035)and peer problems (0.026) of HI children its highly significant found of behavioral problems, so 65% of hearing impaired children had communication problems with others and environment. The teachers facing many problems when deals with HI but the most common one difficult when communicate with them because the limited capabilities available and modern educational methods for teaching the HI children. Conclusions: The majority of hearing impaired children have congenital cause for their hearing loss. Behavior problems appear more common in children with hearing loss and communication problems. The vast majority of teachers agree that there are problems facing students with hearing impairment, and these difficulties need to be dealt with the benefit of their children and the community as a whole.